Characterization of the first report of Mycobacterium timonense infecting an HIV patient in an Ecuadorian hospital. (16th July 2014) - Zurita, J.; Ortega‐Paredes, D.; Mora, M.; Espinel, N.; Parra, H.; Febres, L.; Zurita‐Salinas, C.; Drancourt, M.
Abstract Mycobacterium timonense is a non‐tuberculous mycobacteria (NTM) described in southern France in 2009, and to our knowledge, not reported again as a human pathogen in indexed literature. The aim of this work was to characterize the first clinical isolate of M. timonense in Ecuador. Time of growth, biochemical tests, thin layer growth test, PCR‐RFLP analysis of the hsp65 gene and MALDI‐TOF spectra analysis were not able to identify the species. The species identification was achieved through sequencing of rrs, hsp65 and rpoB genes. The results highlight the necessity to set up a sequencing method to identify emerging NTM in Ecuadorian clinical facilities.